International comparisons, domestic influences and where to next? The case of Irish meat consumption. (November 2022) - Henchion, Maeve; McCarthy, Mary; Zimmermann, Jesko; Troy, Declan J.
Abstract: Meat consumption internationally is driven by many common factors. While this broadly results in similar temporal trends, diversity in how these factors play out locally is evident. Drawing on secondary data sources, this paper illustrates this by comparing Irish meat consumption with other geographies. It illuminates the differential impact of significant shocks, e.g. the BSE crises, and socio-cultural factors on consumption. With increased attention on sustainability, how motivations relating to health, the environment and animal welfare will influence consumption is likely to vary across countries. Questions arise as to how strategies such as "less but better" will evolve, with available options including changing production parameters, producing meat-blended products, premiumisation and meat reduction. Given that the demand for meat stems as much from its traditional role in cultural practices as it does from satisfying individual needs, the extent to which consumer needs are being met by current offerings will change as the position held by meat in society changes. Highlights: Meat consumption is driven by factors that have different impacts locally. Socio-cultural factors result in beef consumption holding steady in Ireland. Sustainability motivations will play out differently in different contexts. A range of options are available to implement "Less but better" strategies. Changes in the role of meat in society presents opportunities and threats.